MODERN METHODS AND TECHNOLOGIES FOR TEACHING A FOREIGN LANGUAGE TO STUDENTS OF THE SPECIALTY “PHYSICAL EDUCATION AND SPORTS” - Khazhgaliyeva, G.Kh. (Жәңгір хан атындағы БҚАТУ, 2024)
The stabilization of the socio-economic situation in the country, the development of international relations of Kazakhstan with countries near and far abroad require the educational system to develop a specialist who has the skills of professional communication with representatives of other cultures. Knowledge of a foreign language is currently not only prestigious, but also necessary for a specialist of any profile. The intensive development of international sports contacts, the increasing competition of foreign rivals at international competitions determines the mastery by students of sports departments of communicative foreign language competence to communicate with foreign colleagues at international competitions, championships, and Olympics. Expansion of scientific connections, trips of specialists abroad to study the experience of foreign colleagues, to participate in international scientific symposiums and conferences also increases the demand for knowledge of a foreign language. In this regard, there are increased requirements for the level of language training of sports specialists. This article touches upon the importance and necessity of learning a foreign language, in particular English, by students of the specialty ―Physical Education and Sports‖. Examples of the use of sports-oriented vocabulary when studying grammar and oral topics are also given in the article.
Khazhgaliyeva G.Kh. MODERN METHODS AND TECHNOLOGIES FOR TEACHING A FOREIGN LANGUAGE TO TUDENTS OF THE SPECIALTY “PHYSICAL EDUCATION AND SPORTS”// Ғылым және білім: Ғылым, зерттеулер, білім: даму тенденциялары: акад. Қ. И. Сәтбаевтың 125 жылдығына арналған халықаралық ғылыми-практ. конф. материалдар жинағы (12 сәуір 2024 ж.) = Наука и образование: Наука, исследования, образование: тенденции развития: сб. мат. междунар. науч.-практ. конф. посвящ. 125-летию акад. К. И. Сатпаева (12 апреля 2024 г.) = Science and education: Science, research, education: development trends: unternational scientific and practical conf. dedicated to the 125th anniversary of acad. K. I. Satpayev (12 april 2024). - Орал: Жәңгір хан атындағы БҚАТУ. - 2024. - № 2 (75) : прил. № 1. - С. 584-591 (Уральск).
Keywords: physical training; educational process; БҚАТУ; конференции; teaching foreign languages; physical education; methods and techniques of teaching; international competitions